2021
DOI: 10.3390/ijms22147380
|View full text |Cite
|
Sign up to set email alerts
|

Further Characterization of Intrastriatal Lipopolysaccharide Model of Parkinson’s Disease in C57BL/6 Mice

Abstract: Parkinson’s disease (PD) is the most common movement disorder, characterized by progressive degeneration of the nigrostriatal pathway, which consists of dopaminergic cell bodies in substantia nigra and their neuronal projections to the striatum. Moreover, PD is associated with an array of non-motor symptoms such as olfactory dysfunction, gastrointestinal dysfunction, impaired regulation of the sleep-wake cycle, anxiety, depression, and cognitive impairment. Inflammation and concomitant oxidative stress are cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 68 publications
3
13
1
Order By: Relevance
“…Of note, neurotoxic PD models also include pesticides and herbicides, with a particular emphasis on rotenone and paraquat, as environmental factors able to affect PD risk (Vaccari et al, 2019). In addition to these neurotoxins, the administration of high-dose lipopolysaccharide (LPS) has been used to generate animal models of PD (Deng et al, 2021). An alternative to the use of neurotoxins is the generation of genetic models.…”
Section: Microglia In Parkinson's Diseasementioning
confidence: 99%
“…Of note, neurotoxic PD models also include pesticides and herbicides, with a particular emphasis on rotenone and paraquat, as environmental factors able to affect PD risk (Vaccari et al, 2019). In addition to these neurotoxins, the administration of high-dose lipopolysaccharide (LPS) has been used to generate animal models of PD (Deng et al, 2021). An alternative to the use of neurotoxins is the generation of genetic models.…”
Section: Microglia In Parkinson's Diseasementioning
confidence: 99%
“…For this purpose, we reviewed articles published from 2015 to 2022 using PubMed, Google Scholar and Scopus, related to keywords ‘neuroinflammation’, ‘LPS’, ‘Alzheimer’s disease’, and ‘Parkinson’s disease’. To induce neuroinflammation in the animal model, LPS can be administered intraperitoneally, stereotaxically and intranasally [ 76 ]. A summary of experimental designs carried out in analyzed research papers is demonstrated in the Table 1 .…”
Section: Technical Aspects Of Lps Model Execution—focus On Ad and Pd ...mentioning
confidence: 99%
“…Thus, the intrastriatal administration of LPS seems to be superior to the intranigral considering their application in neurodegeneration studies [ 9 ]. Deng and colleagues characterized in the detail the intrastriatal LPS model of PD [ 76 ]. They administered 10 μg of LPS unilaterally and then, after 4 and 8 weeks, behavioral tests were conducted.…”
Section: Technical Aspects Of Lps Model Execution—focus On Ad and Pd ...mentioning
confidence: 99%
“…All the surgical procedures were conducted according to recent studies [21]. Briefly, the mice were deeply anaesthetised via inhalation of isoflurane and mounted onto the stereotaxic frame (motorized stereotaxic apparatus, Stoelting, USA).…”
Section: Stereotaxic Surgerymentioning
confidence: 99%
“…In our recent work, we characterised the intrastriatal LPS model of PD which is beneficial for understanding the neuroinflammatory aspect of the disease [21], and for inves-tigating the efficacy of antioxidants and anti-inflammatory compounds. For this study, we selected to further explore edaravone and curcumin which have been shown to have neuroprotective effects in-vivo due to their antioxidant and anti-inflammatory properties [22][23][24].…”
Section: Introductionmentioning
confidence: 99%